Can Company Value Moderate Stock Return: Evidance Southeast Asia Banking - Denny Kurnia (CV ODIS, 2022)
This study aims to determine the effect of Return On Assets, Current Ratio and Debt to Equity Ratio on stock returns moderated by firm value. This study uses the object of the banking sub-sector companies on the Southeast Asian Stock Exchange for the period 2012-2019. The sampling method used in this study using purposive sampling technique obtained 9 companies that present complete financial statements, so that obtained as many as 72 samples. The analytical techniques used are descriptive statistical analysis, classical assumption test, MRA, multiple linear regression, t test, and f test. The results partially conclude that Return On Assets has no significant effect on Stock Return, Current Ratio has no significant effect on Stock Return, and Debt to Equity Ratio has no significant effect on Stock Return. The results of the study simultaneously Return On Assets, Current Ratio, and total Debt to Equity Ratio simultaneously have no significant effect on Stock Return. The results of the MRA show that the Price Earning Ratio does not moderate Return On Assets to Stock Return, Price Earning Ratio does not moderate the Current Ratio to Stock Return, and Price Earning Ratio does not moderate the Debt to Equity Ratio to Stock Return.